Pengaruh Sosialisasi Politik Melalui Proses Belajar Mengajar (PBM) Dan Kesadaran Politik Mahasiswa Ilmu Pemerintahan Terhadap Partisipasi Politik - Agus Supatno; I Ketut Gunawan; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine and analyze the effect of political socialization through the teaching and learning process and the political awareness of Government Science students on political participation. This research was conducted at Mulawarman University with a sample of 2019 and 2020 Government Science students totaling 67 people. Using the technique of Probability Sampling or Simple Random Sampling. Furthermore, research data was obtained by distributing questionnaires online due to the Covid 19 pandemic situation, then analyzed using the Product Moment correlation coefficient, Partial Correlation analysis, Multiple Linear Regression analysis, and Coefficient of Determination analysis. Then after using a series of statistical test results in the results of the correlation coefficient analysis, the relationship between the three variables was obtained, meaning that political socialization through the teaching and learning process and political awareness has a positive and significant influence on political participation. Then by calculating the coefficient of determination it is known that political participation is influenced by political socialization through the teaching and learning process and political awareness of students at Mulawarman University by 30.7% while 69.3% is influenced by other factors that are not included in the focus of this study.